(untitled) (Research, Society and Development, 2024)
Thalassemia is a set of genetic anomalies produced by an inadequate hemoglobin synthesis, the illness rank goes from symptomatology to fetal death. This case was studied and its main target includes to highlight clinical aspects, diagnosis treatment and patient´s quality of life. Data was gathered from patient´s medical record and the NCBI served as reference source. The patients presents anemia with hemoglobin deficiency, hematocrit, VCM, HCM, and CHCM. The total serum iron levels and saturation percentage are markedly diminished. Besides the high resolution capillary electrophoresis indicates an abnormal pattern with suggestive bands of beta thalassemia. In the week 32, a fetal growth control ultrasound detected a profile disturbance with a Doppler study abnormal placental fetus. The diagnosis indicates intrauterine growth restriction phase 1 and the gestation has to be ended in the week 37. The neonatal result is and under weight new born. These kind of patients require a multidisciplinary approach that includes an exhaustive monitoring, a personalizad prenatal care and careful child birth planification.